Theoretically informed gender analysis for gambling harm reduction: a New Zealand study - Katie Palmer du Preez (BMC, 2021)
Abstract Background Gambling harm affects men and women relatively equally, and gender influences the social determinants of gambling harm. Responses to preventing and minimising women’s gambling harm have been shaped and constrained by population research identifying male gender as a key risk factor for gambling problems. Gender analysis in gambling studies is rare and has lacked theoretical underpinning and coherence, limiting possibilities for gender-responsive and gender-aware harm prevention and reduction activities. Methods Two influential qualitative studies of gambling harm in New Zealand (involving total n = 165 people who gambled, affected others, community leaders, gambling and community support service providers, policy makers and academics) neglected to explore the role of gender. This study revisited data collected in these studies, using thematic analysis informed by feminist social constructionist theory. The overarching research questions were: How do gender-related issues, notions and practices influence women’s gambling related harm? What are the implications for women’s gambling harm reduction? Results Women’s socio-cultural positioning as primary caregivers for families and children constrained their ability to access a range of recreational and support options and increased the attractiveness of local gambling opportunities as accessible and ‘safe’ outlets for stress reduction. Patriarchal practices of power and control within family contexts operated to maintain gambling behaviour, shut down alternative recreational opportunities, and limit women’s autonomy. Consideration of these themes in relation to current health promotion practice in New Zealand revealed that national programmes and strategies appear to be operating without cognisance of these gender dynamics and therefore have the potential to exacerbate or cause some women harm. Conclusions This study demonstrates the value of theoretically informed gender analysis for gambling harm reduction research, policy and practice. International guidelines for gender-aware and gender-responsive health research and practice should be engaged as a foundation for strategic and effective gambling harm reduction programmes, projects, research and policy, and as an essential part of developing and implementing interventions for gambling harm.